1999
DOI: 10.1093/clinchem/45.10.1747
|View full text |Cite
|
Sign up to set email alerts
|

Increased Fetal DNA Concentrations in the Plasma of Pregnant Women Carrying Fetuses with Trisomy 21

Abstract: Background: The recent discovery of the presence of circulating cell-free fetal DNA in maternal plasma opens up new prenatal diagnostic applications and provides new avenues for clinical investigation. It is of research and potential diagnostic interest to determine whether fetal trisomy 21 may be associated with quantitative abnormalities of circulating fetal DNA in maternal plasma. Methods: Maternal plasma samples were prospectively collected from two centers situated in Hong Kong and Boston. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
1
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(95 citation statements)
references
References 18 publications
6
84
1
4
Order By: Relevance
“…However, these findings are inconsistent, as some studies report no link between parity and subsequent autoimmune disease [98]. Several pregnancy complications are associated with higher detectable fetal cells circulating in the maternal blood, including preeclampsia, abnormal karyotype and miscarriages [19][20][21][22].…”
Section: Pregnancy Is Associated With Changes In Autoimmune Disease Pmentioning
confidence: 99%
“…However, these findings are inconsistent, as some studies report no link between parity and subsequent autoimmune disease [98]. Several pregnancy complications are associated with higher detectable fetal cells circulating in the maternal blood, including preeclampsia, abnormal karyotype and miscarriages [19][20][21][22].…”
Section: Pregnancy Is Associated With Changes In Autoimmune Disease Pmentioning
confidence: 99%
“…[1][2][3] Fragments of cfDNA are released from dead cells and are present at low concentrations in body fluids, including plasma, serum, cerebrospinal fluid, and urine. 4,5 Circulating cfDNA is detectable in the plasma and serum of healthy individuals, but its levels increase after acute physical exercise, 6 during pregnancy, 7,8 and under pathologic conditions associated with increased cell death, such as inflammation, 9 myocardial infarction, 10,11 burns, 12 and transplantation rejection. 13,14 Circulating cfDNA levels are also drastically increased in patients with various cancers.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that a large fraction of these molecules occurred in a soluble form in the maternal plasma. Interestingly, the levels of cell-free fetal deoxyribonucleic acid (cffDNA) were shown to be altered in pregnancies affected by trisomy 21 (Lo et al, 1999;Zhong et al, 2000;Farina et al, 2003). Subsequently, placental-specific cell-free mRNAs species were detected in the maternal plasma (Poon et al, 2000).…”
Section: Introductionmentioning
confidence: 99%